2005
DOI: 10.1007/s11262-005-1785-y
|View full text |Cite
|
Sign up to set email alerts
|

A 45-Nucleotide Insertion in the NS2 Gene is Responsible for the Cytopathogenicity of a Bovine Viral Diarrhoea Virus Strain

Abstract: Cytopathogenicity (cp) markers have recently been investigated in the genomes of field isolates of bovine viral diarrhoea virus (BVDV). Most of the isolates originated from mucosal disease (MD) cases observed after vaccination with a live attenuated vaccine, termed here BVDV-X. The NS2-3 genes of these isolates and of the vaccine proved to be identical, including a 45-nucleotide (nt) viral insertion at nt position 4355. The insertion originated from the NS4B/5A junction region of the BVDV genome. Interestingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
2
3
1
Order By: Relevance
“…Thus, an insertion of cellular origin (14), or 27-nt and 45-nt insertions of viral sequences of the NS2 and the NS4B-NS5B junction regions were found in the BVDV-1b strain Cp7 and in several vaccine-derived viruses, respectively (14, 15). In accordance with these reports (15, 16), replacing the entire NS2 region of SuwaNcp with the corresponding region of SuwaCp yields a cytopathic virus. However, whether the insertion alone or only in combination with the point mutations in NS2 is responsible for the cp phenotype remains to be determined.…”
Section: Genome Announcementsupporting
confidence: 82%
“…Thus, an insertion of cellular origin (14), or 27-nt and 45-nt insertions of viral sequences of the NS2 and the NS4B-NS5B junction regions were found in the BVDV-1b strain Cp7 and in several vaccine-derived viruses, respectively (14, 15). In accordance with these reports (15, 16), replacing the entire NS2 region of SuwaNcp with the corresponding region of SuwaCp yields a cytopathic virus. However, whether the insertion alone or only in combination with the point mutations in NS2 is responsible for the cp phenotype remains to be determined.…”
Section: Genome Announcementsupporting
confidence: 82%
“…It is worth noting that this cleavage site is located right downstream of the nine aa insertion of the CP7 (). Interestingly, previous studies have identified insertions of a similar size in several other cp isolates at highly similar NS2 positions, one of which was shown to have comparable effects in terms of NS2-3 cleavage and cytopathogenicity as the CP7 insertion [45, 46]. Remarkably, we did not detect any obvious effect of the nine aa insertion on the efficiency of the internal NS2 cleavage in our experiments (), despite the fact that the CP7 insertion is located directly upstream of the cleavage site in NS2 recognized by the NS3/4A protease.…”
Section: Resultscontrasting
confidence: 44%
“…3a). Interestingly, previous studies have identified insertions of a similar size in several other cp isolates at highly similar NS2 positions, one of which was shown to have comparable effects in terms of NS2-3 cleavage and cytopathogenicity as the CP7 insertion [45,46]. Remarkably, we did not detect any obvious effect of the nine aa insertion on the efficiency of the internal NS2 cleavage in our experiments (Fig.…”
Section: Cleavage Within Bvdv Ns2 Occurs At a Conserved Leucine-glycine Motifsupporting
confidence: 54%
See 1 more Smart Citation
“…18 Another possibility is that the PI animal was superinfected, most likely with a homologous antigenically related CP BVDV strain 5, 6, 20 or even a heterologous strain. 2, 17 There is no possibility that the superinfecting virus could have been vaccine-derived, 1, 16 because the only vaccine used in this herd was inactivated.…”
mentioning
confidence: 99%